Plants! - Iasevoli, Brenda (New York : HarperCollins, 2006)
Simple text and photographs provide an introduction to vegetation; describing how seeds grow and how plants get water; explaining how a Venus flytrap eats; and including over thirty fun facts.
2.0
K-3
Keywords: Plants -- Juvenile literature; Plants; Plants